Fasting Ramadan in Yemeni Patients with Type 1 and Type 2 Diabetes: A Comparative Study on the Ability to Fast in 2 Consecutive years - Al-Sharafi BA; Mohsen DF; Almurtadha AS (Diabetes, Metabolic Syndrome and Obesity, 2025)
Butheinah A Al-Sharafi,1 Dares Fateh Mohsen,2 Ahlam S Almurtadha1 1Department of Internal Medicine, School of Medicine and Health Sciences, Sana’a University, Sana’a, Yemen; 2Department of Internal Medicine University of Science and Technology, Sana’a, YemenCorrespondence: Butheinah A Al-Sharafi, Department of internal medicine, School of medicine and Health Sciences, Sana’a university, Sana’a, Yemen, Email balsharafi@hotmail.comBackground: Fasting is obligatory for all healthy adult Muslims in the month of Ramadan, one of Islam’s five pillars. Over 50 million diabetics fast annually, emphasizing the necessity for specialized care.Aim: The study focused on the ability of diabetic patients in Yemen too fast for two consecutive years during Ramadan.Methodology: A total of 573 Patients (343 females and 230 males, including 19 adolescents aged 12– 19 years) participated in the study. The patients answered a questionnaire regarding how they fasted in 2022 and after fasting Ramadan in 2023 they were contacted to ask how they had fasted and reasons for breaking their fast. The patients’ medications were adjusted according to the Diabetes and Ramadan guidelines (DAR). Statistical analysis was used for ANOVA and chi-square tests to investigate correlations and differences. Frequencies and percentages were used to describe qualitative data. Binary logistic regression analysis was used to calculate odds ratio and 95% confidence intervals.Results: The percentage of patients that fasted all of Ramadan was 84% and among those that broke their fast, hyperglycemia and hypoglycemia were the primary reasons for this. We found that there were significant associations between breaking fasting patterns and age (p = 0.023), type 1 diabetes (p = 0.041), insulin use (p = 0.017), and those that had a history of breaking their fast in a previous year (p< 0.001). The levels of HbA1c, duration of diabetes, body mass index (BMI), and level of education were not significantly related to developing hypoglycemia.Conclusion: The study shows different factors affecting fasting Ramadan in diabetic patients in Yemen over 2 years. It emphasizes the need for personalized care plans, focused educational initiatives for teenagers and adults with diabetes, and ongoing initiatives to improve the health of Yemeni people with diabetes for fasting during Ramadan.Keywords: Ramadan fasting, diabetic patients, glycemic control, hypoglycemia prevalence, fasting behavior, diabetes care